The "Rebound Effect" as a Devolutive Figure of Patriarchal-colonial Backlash. (Palimpsesto, 2024)
The essay addresses the socio-cultural implications of the sex-politics of the normative ideal promoted by the patriarchal-colonial backlash for sexual diversity and dissidence in Chile through the analytical potential identified in the notion of "rebound effect". In the light of socio-empirical and socio-theoretical sources, the essay focuses on the demystification of the assumptions of the "soft coup" hypothesis, mobilized by ultra-right-wing actors in academic and communicational media to explain the emergence of the Chilean October uprisings. It is concluded that the performativity of the enunciative acts that adhere to the studied object stimulates the managerial reproduction of the conditions of inequality (anti-LGBTIQ+ and anti-gender) qua semantics of rectification.
Keywords: patriarchal-colonial backlash; sexual diversity and dissidence; rebound effect; soft coup